Adenosine Triphosphate Test After Cryothermal Pulmonary Vein Isolation: Creating Contiguous Lesions Is Essential for Eliminating Dormant Conduction. (3rd August 2015) - MIYAZAKI, SHINSUKE; TANIGUCHI, HIROSHI; NAKAMURA, HIROAKI; HACHIYA, HITOSHI; ICHIHARA, NOBORU; ARAKI, MAKOTO; KUROI, AKIO; TAKAGI, TAKAMITSU; IWASAWA, JIN; HIRAO, KENZO; IESAKA, YOSHITO
Dormant Conduction After Cryothermal PVI Background Adenosine triphosphate (ATP) testing reveals dormant pulmonary vein (PV) conduction after electrical PV isolation (PVI). This study aimed to evaluate the incidence of latent PV conduction after cryothermal PVI. Methods Fifty‐four consecutive paroxysmal atrial fibrillation patients undergoing cryothermal PVI were prospectively enrolled. PVI was performed with one 28‐mm second‐generation balloon using a 3‐minute freeze technique, and touch‐up lesions were created by focal cryothermal applications. ATP testing was performed following PVI with a 20‐mm circular mapping catheter placed in each PV. Results Of 217 PVs, 205 (94.5%) were isolated using a cryoballoon, and 12 required additional focal ablation. ATP testing was performed in 46 patients for 173 and 8 PVs, which were isolated by cryoballoons and focal ablation, respectively. No dormant PV conduction was provoked in any PVs, which were isolated by cryoballoons, whereas 4 (50.0%) out of 8 PVs requiring focal ablation had transient ATP‐provoked reconnections (0 vs. 50.0%, P < 0.0001) with a median duration of 11.3 (10.7–17.1) seconds. The latent PV conduction site was identical to the residual conduction gap site after cryoballoon ablation in all. All latent conduction was successfully eliminated by 2 (2.0–9.5) additional focal applications. At a mean follow‐up of 7.7 ± 1.6 months, 81.5% of the patients were arrhythmia free after a single procedure. Conclusions No dormant PV conduction was provoked in PVs, which were isolated by 28‐mm second‐generation cryoballoons, but was provoked in 50% of PVs, which were isolated by focal cryoablation. These findings suggest that creating contiguous lesions is essential for eliminating dormant conduction in cryothermal ablation.